Evaluation of Reservoir Quality of the Mishrif Formation in Faihaa Oil Field - Alani, Zuhoor J. (Journal of Petroleum Research and Studies, 2024)
Two wells are selected in the Faihaa field (FH-1 and FH-2) to study the petrophysical properties and evaluate the reservoir units of the Mishrif Formation. The cross plots of density-neutron and M-N show that the Mishrif Formation consisting mainly of limestone with calcite as the main mineral with the presence of dolomite in very few percentages and points within the range of secondary porosity and gas. Petrophysical properties were determined and plotted as computer processing interpretation (CPI) such as shale volume, porosity, water saturation, and hydrocarbon saturation by using Techlog software and showing that FH-2 has a good petrophysical property than FH-1. The main reservoir units in both wells are MA, MB, MC, MD and ME. The MD unit considered as the best reservoir unit with good of reservoir quality compared to the rest of the units due to good porosity values and low values of shale volume and water saturation. each of the MB and MC units has a good reservoir quality in FH-2 and the lowest reservoir quality in FH-1, while both the MA and ME units consider the weakest units that have poor reservoir quality, especially the MA unit which has a few thicknesses with high shale volume values.